Nurturing Feedback and its Impact on Self-Efficacy, Empowerment, and Professional Growth in Educational and Corporate Environments - Bejtic, Zinka (International Journal of Advanced Corporate Learning (iJAC), 2024)
This study examines the impact of feedback quality in design education on students' self-efficacy. It argues that nurturing feedback can positively influence students' self-efficacy, leading to increased effort, perseverance, and eagerness to embrace challenges. A case study conducted in a senior design studio course at the American University of Sharjah (UAE) explores the effects of feedback. It proposes strategies to transform it into a nurturing tool for students' self-efficacy. The insights gained provide valuable guidance for all instructors involved in educational environments where feedback plays a pivotal role in students' growth and development. Furthermore, the findings have broader implications for the corporate design sector, emphasizing the importance of nurturing feedback to empower employees and foster their professional growth. Empowered employees are more likely to embrace challenges, take initiative, and contribute to organizational success, making nurturing feedback a vital factor in promoting a positive and productive work environment.